1954
DOI: 10.1021/jf60036a006
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Fluorine, Fluorine Acquired by Forage Cultures in Outdoor and Washed Atmospheres at Columbia, Tenn.

Abstract: 47.7% in the high protein dietary lot to 55.0% in the low protein group receiving Aureomycin. From these data the highprotein dietary levels appear to decrease the total solids content of hams; however, the variance mean squares were not significant, but appreciable. The observation that the hams having the greatest protein content also have the greatest water (volatile matter) content is in agreement with the knowledge that muscle contains more water than nonmuscular tissues, such as fat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1955
1955
1971
1971

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…No fluorine contamination occurred in the vegetation grown in pot cultures 1 Present address, 4201 Twenty-eighth Ave., No., St. Petersburg, Fla. and low occurrences of fluorine in at Knoxville, but fluorine content increased during further growth outdoors at the Middle Tennessee Station, although not in the transported vegetation grown in the fluorine-free atmosphere of an adjacent chamber (7). Thus the transported plants acquired fluorine from both soil and air during their 21 days' growth at Columbia, whereas the plants in the chamber derived fluorine solely from the soil.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…No fluorine contamination occurred in the vegetation grown in pot cultures 1 Present address, 4201 Twenty-eighth Ave., No., St. Petersburg, Fla. and low occurrences of fluorine in at Knoxville, but fluorine content increased during further growth outdoors at the Middle Tennessee Station, although not in the transported vegetation grown in the fluorine-free atmosphere of an adjacent chamber (7). Thus the transported plants acquired fluorine from both soil and air during their 21 days' growth at Columbia, whereas the plants in the chamber derived fluorine solely from the soil.…”
mentioning
confidence: 88%
“…The washdown of fluorides and their fixation by Spanish moss have served to indicate atmospheric emissions deemed responsible for abnormal incidence of fluorine in nearby field crops (6) and a resultant economic problem in livestock farming (5). The quantities of fluorine carried by single rainfalls at six locations in 1948, 1949, and 1950 were reported in 1952 (8) and, in 1951, atmospheric occurrences were determined also through the quantities fixed in month-long exposures of Spanish moss at multiple locations in relation to industrial emissions in three Tennessee counties (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Absorption is greatest .with the addition of soluble fluorides to light, sandy soils with little organic matter, but even so, much of the absorbed fluoride remains in the root system (25)(26). In contaminated areas fluorides are deposited on the foliage, and it has been shown that gaseous fluorides, in particular hydrogen fluoride, are readily absorbed by the leaves (27).…”
Section: Fluoride Intake From Foodmentioning
confidence: 99%
“…After fumigation the unlimed leaves of gladiolus showed the characteristic tip scorch with a chlorotic region of about 3 to 5 mm between the brown and (9,10), the respiration rate increased with fluoride concentration up to a certain level and rapidly declined approaching death of the tissue.…”
mentioning
confidence: 99%